Telemedicine: new technology, new promises? - Devanbu, Vinoth Gnana Chellaiyan; A Y, Nirupama; Taneja, Neha (Indian Journal of Community Health, 2019)
Telemedicine has emerged to be key player in healthcare delivery in underserved areas. Successful telemedicine projects in India like the Aravind tele-ophthalmology network, the Kerala Onconet project and the Amrita mobile telemedicine unit are an inspiration for future endeavors. While improved access to healthcare, decreased healthcare costs and time saving were lauded as the strengths of telemedicine, the fact that very few reliable literature and statistics is available for the cost-effectiveness of telemedicine and the need for specialized equipment and training are weakening the potential telemedicine boom. As reluctance for acceptance by the public, lack of medicolegal protocols and an authoritative regulatory body are threatening the future of telemedicine, we hope that the establishment of virtual medical centers and international collaboration in the field of telemedicine and its inclusion in government programmes like PMJAY- Ayushman Bharath will prove to be a step towards a brighter future for telemedicine in India.